Optimization of peptide substrates for botulinum neurotoxin E improves detection sensitivity in the Endopep-MS assay - Wang, Dongxia (Anal Biochem, 2014)
Botulinum neurotoxins (BoNTs) produced by Clostridium botulinum are the most poisonous substances known to mankind. It is essential to have a simple, quick and sensitive method for the detection and quantification of botulinum toxin in various media, including complex biological matrices. Our laboratory has developed a mass spectrometry-based Endopep-MS assay that is able to rapidly detect and differentiate all types of BoNTs by extracting the toxin with specific antibodies and detecting the unique cleavage products of peptide substrates. Botulinum neurotoxin type E (BoNT/E) is a member of a family of seven distinctive BoNT serotypes (A to G) and is the causative agent of botulism in both humans and animals. To improve the sensitivity of the Endopep-MS assay, we report here the development of novel peptide substrates for the detection of BoNT/E activity through systematic and comprehensive approaches. Our data demonstrate that several optimal peptides could accomplish 500-fold improvement in sensitivity compared to the current substrate for the detection of both not trypsin-activated and trypsin-activated BoNT/E toxin complexes. A limit of detection of 0.1 mouseLD(50)/mL was achieved using the novel peptide substrate in the assay to detect not trypsin-activated BoNT/E complex spiked in serum, stool and food samples.